From linoleic acid to hexanal and hexanol by whole cell catalysis with a lipoxygenase, hydroperoxide lyase and reductase cascade in Komagataella phaffii - Hashem, Chiam; Hochrinner, Julius; Bürgler, Moritz B.; Rinnofner, Claudia; Pichler, Harald; Winkler, Margit (Frontiers in Molecular Biosciences, 2022)
Green leaf volatiles (GLVs) cover a group of mainly C6-and C9-aldehydes, -alcohols and -esters. Their name refers to their characteristic herbal and fruity scent, which is similar to that of freshly cut grass or vegetables. Lipoxygenases (LOX) catalyze the peroxidation of unsaturated fatty acids. The resulting hydroperoxy fatty acids are then cleaved into aldehydes and oxo acids by fatty acid hydroperoxide lyases (HPL). Herein, we equipped the yeast Komagataella phaffii with recombinant genes coding for LOX and HPL, to serve as a biocatalyst for GLV production. We expressed the well-known 13S-specific LOX gene from Pleurotus sapidus and a compatible HPL gene from Medicago truncatula. In bioconversions, glycerol induced strains formed 12.9 mM hexanal using whole cells, and 8 mM hexanol was produced with whole cells induced by methanol. We applied various inducible and constitutive promoters in bidirectional systems to influence the final ratio of LOX and HPL proteins. By implementing these recombinant enzymes in Komagataella phaffii, challenges such as biocatalyst supply and lack of product specificity can finally be overcome.